HUBUNGAN MOTIVASI BELAJAR SISWA DAN PENDAPATAN ORANG TUA TERHADAP MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI SMK NEGERI 1 PALEMBANG - Devi Saputri; Syarwani Ahmad; Neta Dian Lestari3 (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
For students who will approve the choice to go to college, of course they will be faced again with the choice of which college to enter and what direction to choose. In its development, students support to continue their studies to higher education by considering the money spent by parents of students who want to go to college. The population in this study were all students of class X Accounting and Financial Institutions sponsored by 143 students. Data collection techniques use questionnaire, observation and documentation techniques. Based on the test results it is undeniably related to student motivation and parents' money towards the interest received by the study in the high school at Palembang State Vocational School 1 This result is strengthened by the value of Fcount 257,013 > Ftable 2.715 or Sig Fcount 0.000 <a = 0.05. Higher success, student learning and parents' money will be even greater towards the interest in continuing their studies to higher education at Palembang State Vocational School 1.Keywords: Motivation to Study, Parent Income, and Interest in Continuing Study to Higher Education